Developing and using classroom assessments - Oosterhof, Albert (Pearson Education, 2009)
This updated, brief, inexpensive book focuses on how to write, construct, and use assessments in the classroom. It continues to take a balanced approach to assessment, involving both traditional and innovative techniques. It includes the development and use of written tests, informal assessments, portfolios, and performance assessments. This balanced approach to assessment is what prospective teachers need when they get into the classroom. Coverage includes integrating assessments into the learning process, showing the implications of research in cognitive psychology and showing how classroom assessments can facilitate transfer of learning and development of problem solving skills. For professionals in the field of Educational Psychology or anyone interested in teaching methods.